HUBUNGAN PERAN ORANG TUA DALAM KEMANDIRIAN ANAK TUNAGRAHITA DALAM ACTIVITIES DAILY LIVING DI SEKOLAH DASAR LUAR BIASA NEGERI KABUPATEN PRINGSEWU TAHUN 2018 - Aulia Rahman; Haldi Adma (Universitas Malahayati Lampung, 2019)
ABSTRACK : CORRELATION PARENTS IN THE INDEPENDENCE OF THE CHILDREN IN THE ACTIVITIES OF THE DAILY LIVING AT THE EXTRAORDINARY ELEMENTARY SCHOOL IN PRINGSEWU DISTRICT 2018 Background : Tunagrahita is a disorder marked by an intellectual function that functions meaningfully below average with an IQ of approximately 70 or lower which starts before the age of 18 years. Activities Daily Living (ADL) is an activity to do routine work daily – such as toilet, meal, dressing, bathing, and moving places. In Lampung Province in 2016, there are about 66,610 school children with disabilities of about 23% of whom are people who are people who have disabilities.Purpose : The role Of parents in the independence Of the Children in ADL (the Activities Of Daily Living) at the Pingsewu State Elementary School in 2018.Methods: Quantitative research type, analytic research Draft with Cross Sectional approach. The population of all parents who have children in Pringsewu District Extraordinary Elementary School is about 35 people. The statistical test used is Chi Square statistical test.Results : Frequency distribution based on the role of parents in Independence ADL with a less than good number of 22 respondents (62.9%), frequency distribution based on child self-reliance about ADL with independent category 19 Respondents (54.3%).Conclusion: There is a relationship of parents with self-reliance (Activities Daily Living) in children at the state Extraordinary elementary school. The analysis result is obtained (P Value = 0.012 α = 0.012) with POR value = 8.889. It is hoped that the Pringsewu state elementary School could continue to develop teaching programs on the independence of Activities Daily Living and such as CHAPTERS/TUBS, bathing activities, dressing activities, eating or drinking activities and activities Moves to train his child to become self-reliant by adding hours of learning, theory and balanced practice and establishing cooperation with the parents of the student disabled so that students get guidance and support is needed at the time at home .